2004
DOI: 10.1088/0022-3727/37/15/022
|View full text |Cite
|
Sign up to set email alerts
|

Grain topology in Ti–6Al–4V welds—Monte Carlo simulation and experiments

Abstract: The importance of topological features of grains in the evolution of grain structure is well recognized in isothermal systems. However, during fusion welding, strong spatial gradients of temperature exist in the heat-affected zone (HAZ), and this region undergoes rapid heating and cooling. The effects of spatial and temporal variations of temperature on the topological class distribution, relationship between size and topology of grains and the interdependence between grain topology and its neighbours are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
(40 reference statements)
1
30
0
Order By: Relevance
“…Figure 3 shows the calculated enhancement factors for the thermal conductivity and viscosity as a function of heat input by using the vorticity-based turbulence model and the proposed Eqs. [13] and [14]. The calculated enhancement factors for thermal conductivity and viscosity by using vorticity-based turbulence also increase with an increase in the heat input per unit length as obtained by Eqs.…”
Section: B Improvement In the Reliability Of The Heat-transfer And Fmentioning
confidence: 53%
See 3 more Smart Citations
“…Figure 3 shows the calculated enhancement factors for the thermal conductivity and viscosity as a function of heat input by using the vorticity-based turbulence model and the proposed Eqs. [13] and [14]. The calculated enhancement factors for thermal conductivity and viscosity by using vorticity-based turbulence also increase with an increase in the heat input per unit length as obtained by Eqs.…”
Section: B Improvement In the Reliability Of The Heat-transfer And Fmentioning
confidence: 53%
“…The calculated enhancement factors for thermal conductivity and viscosity by using vorticity-based turbulence also increase with an increase in the heat input per unit length as obtained by Eqs. [13] and [14]. The reasons for slightly lower values of the average enhancement factors for thermal conductivity and viscosity by the vorticitybased turbulence model compared to Eqs.…”
Section: B Improvement In the Reliability Of The Heat-transfer And Fmentioning
confidence: 94%
See 2 more Smart Citations
“…Significant advances were made by Debroy et al with a three-dimensional (3D) weld simulation. [12][13][14][15] Their studies demonstrated good agreement with experimental grain size distributions at various distances from the centerline of the FZ. Debroy and co-workers focused their analysis on the heat-affected zone (HAZ) surrounding the FZ and excluded the FZ from their simulation domain.…”
Section: Introductionmentioning
confidence: 57%